Teacher Evaluation of Islamic Religious Education Subjects as Improving the Quality of Student Learning at SDIT UMMI Bengkulu City (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this evaluation research is to explore in depth the performance of teachers in learning activities as material for evaluating the learning system at SDIT UMMI Bengkulu City. In the standard learning implementation process which consists of 3 stages or dimensions, namely: planning the learning process, implementing the learning process, and assessing the learning process. Methodology: This research uses a qualitative approach and descriptive data type. This research was conducted at SDIT UMMI Bengkulu City. Data collection is carried out using interview techniques or questionnaires. In this research, the researcher collaborated with 2 teachers and the Head of SDIT UMMI Bengkulu City. Main Findings: Based on the results of interviews with Islamic Religious Education subject teachers at SDIT UMMI Bengkulu City, planning, implementation and assessment were good. Likewise, attention from foundations and school principals who give full attention to teachers so that they can continue to develop their potential and improve their teaching performance. Novelty/Originality of this study: Evaluation is a measuring tool and an effort to determine the level of success achieved. Evaluation activities are able to provide information about deficiencies or possible errors that need to be corrected in the future. Evaluation activities can encourage teachers to improve the quality of education in the future. This research is a novelty from previous research as a reference for improving the quality of student learning in elementary schools.